2003
DOI: 10.1097/00002030-200303280-00007
|View full text |Cite
|
Sign up to set email alerts
|

A phase II clinical study of the long-term safety and antiviral activity of enfuvirtide-based antiretroviral therapy

Abstract: Self-administration of enfuvirtide is not associated with unexpected toxicities for up to one year, and combined with oral antiretroviral drugs was associated with a significant decrease in HIV RNA and an increase in CD4 cell counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 26 publications
1
91
0
Order By: Relevance
“…Although several HIV-1 entry inhibitors have been evaluated in clinical trials and have shown promising prospects for therapy (1,28), the only entry inhibitor licensed to date is the fusion inhibitor enfuvirtide (ENF; also called T20), which has shown potent antiviral activity in patients, resulting in sustained viral load reduction when used in combination with an optimized background regimen of protease and/or reverse transcriptase inhibitors (21)(22)(23). Similar to results with other antiviral agents, however, ENF-resistant HIV-1 variants may emerge under the selective pressure of ENF (26,32,39,42) whenever the treatment fails to completely suppress viral replication in vivo.…”
mentioning
confidence: 99%
“…Although several HIV-1 entry inhibitors have been evaluated in clinical trials and have shown promising prospects for therapy (1,28), the only entry inhibitor licensed to date is the fusion inhibitor enfuvirtide (ENF; also called T20), which has shown potent antiviral activity in patients, resulting in sustained viral load reduction when used in combination with an optimized background regimen of protease and/or reverse transcriptase inhibitors (21)(22)(23). Similar to results with other antiviral agents, however, ENF-resistant HIV-1 variants may emerge under the selective pressure of ENF (26,32,39,42) whenever the treatment fails to completely suppress viral replication in vivo.…”
mentioning
confidence: 99%
“…Thompson et al (2006) measure the steady state pharmacokinetic properties of enfuvirtide administered 90 mg bid and 180 mg qd in ∼20 patients. Lalezari et al (2003b) report similar data for 45 mg bid from ∼70 patients. We reproduce the reported mean steady state concentration-time data in Fig.…”
Section: Subcutaneous Administrationmentioning
confidence: 61%
“…6A) may lie within the uncertainties. We also compare our model predictions with reported values of C max , C trough , and AUC for the 45 mg bid (Lalezari et al, 2003b), 90 mg bid, and the 180 mg qd dosing regimens (Fig. 7).…”
Section: Subcutaneous Administrationmentioning
confidence: 95%
See 2 more Smart Citations